Challenges of Interference and Disinformation in Italy: Countering New Threats to National Security - Elena A. Maslova (Современная Европа)
The focus of this article is the phenomenon of disinformation and foreign interference in Italy. The aim of the study is to examine Italy's approach to countering interference and combating disinformation. The article presents a scientific discussion on the terminology of the concept of “interference” and demonstrates that the lack of a definition does not detract from the results obtained on the topic. In countering interference in the broadest sense, as a threat to national security and the constitutional order of the country, Italy relies primarily on the national resources, where the main body is a special structure ‒ the System for the Security of the Republic. The Special Parliamentary Committee for the Security of the Republic plays an important role as well. The issue of disinformation as an intervention tool has received more attention from researchers and institutions. The EU clearly distinguishes between “disinformation” and “misinformation”. In 2023, Italy was the first EU country to spread disinformation (in terms of the amount of deleted content from social media). In combating disinformation, Italy relies on the EU's guidelines and experience, transferring content moderation responsibilities to the EU level. The EU reacts with harsh methods, resorting to content removal and blocking of resources. Thus, the more Italy delegates its information security to the European Union, the more Rome involves in the information confrontation and war of narratives between Brussels and Moscow.